1994
DOI: 10.1038/nsb1194-782
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the pleckstrin homology domain from dynamin

Abstract: The pleckstrin homology (PH) domain is a conserved module present in many signal transducing and cytoskeletal proteins. Here we report the 2.8 A crystal structure of the PH domain from dynamin. This domain consists of seven beta-strands forming two roughly orthogonal antiparallel beta-sheets terminating with an amphipathic alpha-helix. The structure also reveals a non-covalent dimeric association of the PH domain and a hydrophobic pocket surrounded by a charged rim. The dynamin PH domain structure is discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(81 citation statements)
references
References 28 publications
2
79
0
Order By: Relevance
“…Interestingly, a variety of PH domains from various other signaling molecules that were bacterially expressed and purified under similar conditions did not show any biological effect when injected in the oocytes, suggesting that the observed effect is specific to the Sos1 PH domain. Different PH domains appear to share a common tertiary structure, although the conservation of their primary sequence is rather limited (2)(3)(4)(5)(6). In this regard, the present results suggest that, in addition to the tertiary structure, the primary structure is an essential factor responsible for the observed biological activity.…”
Section: Sos1 Ph Cooperates With Normal Ras Proteins and Is Blocked Bmentioning
confidence: 57%
See 1 more Smart Citation
“…Interestingly, a variety of PH domains from various other signaling molecules that were bacterially expressed and purified under similar conditions did not show any biological effect when injected in the oocytes, suggesting that the observed effect is specific to the Sos1 PH domain. Different PH domains appear to share a common tertiary structure, although the conservation of their primary sequence is rather limited (2)(3)(4)(5)(6). In this regard, the present results suggest that, in addition to the tertiary structure, the primary structure is an essential factor responsible for the observed biological activity.…”
Section: Sos1 Ph Cooperates With Normal Ras Proteins and Is Blocked Bmentioning
confidence: 57%
“…Included among the many PH-containing proteins described so far are several that participate in Ras signaling pathways. Despite having a rather limited primary sequence consensus identity, the PH domains from different proteins appear to share a common tertiary structure consisting of seven antiparallel ␤-sheets and a carboxyl-terminal amphiphilic ␣ helix (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…Although isolated Dyn1PH crystallized as a dimer (33,53), x-ray scattering (33), and analytical ultracentrifugation (54) studies showed that it is monomeric at concentrations up to 10 mg/ml (680 M), and tends to oligomerize only above 1 mM (54). Oligomerization of Dyn1PH therefore requires that it is present in a molecule that self-associates through other interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of several PH domains has been determined (Ferguson et al, 1994(Ferguson et al, , 1995Fushman et al, 1995;Hyvonen et al, 1995;Macias et al, 1994;Timm et al, 1994;Yoon et al, 1994). These structures exhibit a common globular fold that consists of seven anti-parallel b strands and an a helix (Gibson et al, 1994;Lemmon et al, 1996).…”
Section: A Structural Model Of the Akt Ph Domainmentioning
confidence: 99%